IMPROVING STUDENTS’ ABILITY IN WRITING NARRATIVE TEXTS USING SHORT ANIMATED STORIES AT CLASS VIII C OF SMP PGRI 30 JAKARTA TIMUR - Millah, Syaeful (LPPM STMIK WIT, 2022)
This research was aimed at improving the writing ability of students of VIII C of SMP PGRI 30 Jakarta Timur. The problem was that they had low writing ability. This particular research was categorized as action research. The actions were implemented in two cycles based on the class schedule. This research involved the 28 students of class VIII C of SMP PGRI 30 Jakarta Timur and the English teacher as the research collaborator. The data of the study were in the forms of qualitative and quantitative data. The qualitative data were obtained by observing the teaching and learning process of writing, interviewing the students of class VIII C and the English teacher, holding a discussion with the collaborator and taking figures and recording videos. Meanwhile, the quantitative data were acquired through the pre-test, the progress test, and the post test. The validity of the data was obtained by applying democratic validity, dialogic validity, catalytic validity and outcome validity. The research findings showed that the use of short animated stories combined with the use of some supporting activities and classroom was proven to be effective to improve the students’ writing ability. It could get students’ attention and increased their learning motivation. It can help the students understand the story better as the video content visual or moving images that can help imagining the real situation in the story. The students who just gained 58.8 in the pre-test, were able to increase their score up to 76.1 in the post test. It indicated that they made a considerable improvement in some aspect of writing skills such as content, organization, vocabulary and grammar and mechanics.